Pemberdayaan Anak Usia 4-10 Tahun Dalam Meningkatkan Mutu Hafalan Al-Qur’an Melalui Program Musabaqah Hifzhil Qur’an Di Desa Cadassari Kec. Tegalwaru Purwakarta - Nugraha, Adam Fauzan; Supendi, Dede (Pendidikan Sejarah FKIP Universitas JAMBI, 2026)
This activity was initiated based on the condition that although the village possesses religious potential through the presence of a Qur’anic Learning Center (TPQ), students still experience various obstacles in memorization, such as lack of fluency in recitation, incorrect sequence of verses, and inconsistency in conducting muraja’ah (revision). Based on these needs, the program was designed to improve the quality of memorization by collaboratively involving various elements of the community, including TPQ teachers, parents, and community leaders. The method used was Participatory Action Research (PAR). The main objective of the program was to enhance the quality of students’ memorization through a series of structured learning and evaluation activities. The PAR method was employed because it encourages the active involvement of all stakeholders, ensuring that each stage of the program was jointly planned and implemented in a participatory manner. The program was carried out over five weeks, consisting of the stages of mapping students’ memorization abilities, providing regular muraja’ah assistance after Maghrib prayer, and conducting evaluations through the Musabaqah Hifzhil Qur’an (MHQ) competition using verse-connection and selected surah recitation methods. The results of the program showed a significant improvement in students’ fluency of memorization, accuracy in verse sequence, and self-confidence in presenting their memorization. Beyond academic outcomes, the program also had a positive impact in strengthening parental involvement in the learning process and fostering a stronger Qur’anic culture within the community. Overall, this community service activity confirms the effectiveness of a participatory approach in improving the quality of Qur’anic learning and in building a sustainable religious education ecosystem..